Research on Technological Pedagogical and Content Knowledge: A Bibliometric Analysis From 2011 to 2020 - Lee, Hung-Ying; Chung, Chi-Yang; Wei, Ge (Frontiers in Education, 2022)
This study was to explore the bibliometric characteristics of TPACK from 2011 to 2020. By using the keyword “TPACK”, the bibliographic references have been retrieved from the Scopus databases (date of search: March 7, 2021). The VOSviewr software tool and Bibliometrix R package were used for information analysis. The results confirmed that there are 700 articles, representing 63 countries and 159 journals scanned. Articles in 2013 were cited the most times, and since 2016, the number of articles is on the rise every year. The USA, Turkey, and Australia were the three leading countries in this field. Most of the articles were published in educational technology journals. The total articles published by American institutions are more than the others, followed by Asian institutions. The most prolific authors are all Asians, followed by Americans. Core themes from the highly-cited articles have been surrounding PCK, teacher education, skill, and pedagogy. The development of TPACK has gradually turned to practical strategies and tried to find strategic ways to facilitate teachers to implement technology-assisted teaching.